ANALISIS PERKEMBANGAN PERBANKAN SYARIAH DI INDONESIA DI MASA PANDEMI COVID-19 - Muhammad Masruron; Nurul Aulia Adinda Safitri (Al Birru: Jurnal Keuangan dan Perbankan Syariah, 2022)
Currently, Islamic banking in Indonesia is able to show good performance. The impact of covid19 has also caused a decrease in demand for sharia business products and a slowdown in the realization of investment. During the covid19 pandemic, the government is trying to implement policies that can help the growth of assets, financing, and deposits for Islamic banking. Several real sectors that have been affected by Covid-19 in the halal industry include Halal value chain and Fyshen Muslim. Vaccination promoted by the government is a tangible form of returning people's activities to normal. Through the vaccination program carried out by the government, it is hoped that it will be able to increase economic growth which was hampered by the Covid-19 pandemic. Keywords : Sharia economy, development of sharia finance, halal industry, and vaccination programs for economic recovery Abstrak Saat ini Perbankan Syariah di Indonesia mampu menunjukan kinerja yang baik.Dampak dari covid19 juga menyebabkan penurunan permintaan produk bisnis syariah dan perlambatan realisasi penanaman modal.pandemi covid19, pemerintah berupaya menerapkan kebijakan yang dapat membantu Pertumbuhan aset, pembiayaan, dan DPK perbankan syariah. Beberapa sektor riil yang terkena dampak covid-19 pada industri halal diantarnaya Halal value chain dan Fyshen Muslim. Vaksinisasi yang digalakkan pemerintah menjadi wujud nyata mengembalikan aktivitas masyarakat kembali normal. Lewat program vaksinisasi yang dilakukan pemerintah diharapkan mampu meningkatkan pertumbuhan ekonomi yang sempat terkendala akibat covid-19. Kata Kunci : Ekonomi syariah, perkembangan keuangan syariah, industri halal, dan program vaksinisasi untuk pemulihan ekonomi